Influência da infecção por papilomavírus humano e da relação sexual sobre a atividade imunológica de células epiteliais endocervicais - Witkin, Steven S.; Linhares, Iara; Giraldo, Paulo; Ledger , Willian J. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Epithelial cells in the human cervix produce and release cytokines in response to external stimuli as well as react to the presence of exogenous cyto kines. These cells, therefore, are components or thc mucosal defense system within the female genital tract. lnfection of cervical epithelial cells with human papillomavirus, and the malignant transformation of these cells, alters their ability to produce and respond to cytokines. Similarly, exposure to semen also changes the immune modulating capabilities of cervical epithelial cells. Sexual intercourse induces transcription of the gene codi og for the 70 kDa heat shock protein in lhe human cervix. This, plus the induclion of interleukin-10 production in lymphoid cells, downregulates genital tract immune defenses.